2000
DOI: 10.1542/peds.105.2.325
|View full text |Cite
|
Sign up to set email alerts
|

School Difficulties at Adolescence in a Regional Cohort of Children Who Were Extremely Low Birth Weight

Abstract: Differences of 13 to 18 points in psychometric measures in ELBW teens compared with controls are both statistically significant and clinically relevant. Decreasing birth weight was associated with increased risk on all measures. The high utilization of special educational resources has economic implications, and the incremental cost attributable to being extremely premature needs to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
266
4
34

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(325 citation statements)
references
References 39 publications
21
266
4
34
Order By: Relevance
“…Furthermore, the magnitude of the differences observed in TAAS scores (1.5SD) were consistent with group differences observed on standardized ability and achievement tests in extremely preterm cohorts. 4,19,22 Using the optimal receiver operating characteristic-determined TAAS cut-off of scores <2.5, the clinical validity of the scale was further demonstrated by the high sensitivity and specificity levels for predicting learning impairment, which far exceeded minimum standards for screening tests. 23 Used concurrently, at least 90% of children with learning impairment were identified as such using the TAAS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the magnitude of the differences observed in TAAS scores (1.5SD) were consistent with group differences observed on standardized ability and achievement tests in extremely preterm cohorts. 4,19,22 Using the optimal receiver operating characteristic-determined TAAS cut-off of scores <2.5, the clinical validity of the scale was further demonstrated by the high sensitivity and specificity levels for predicting learning impairment, which far exceeded minimum standards for screening tests. 23 Used concurrently, at least 90% of children with learning impairment were identified as such using the TAAS.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that infants born very prematurely show difficulties in academic learning (e.g. Saigal et al, 2000;Grunau et al, 2002) that persist through adolescence (e.g. Hack et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…58 Certain studies have documented worse performance in verbal reasoning tests, with 24% of lack of accuracy at reading and 48% of inadequate comprehension when reading, 63 but the majority of authors point out that very low birth weight children, particularly those born at less than 750 g, exhibit compromise in areas of educational ability which can prejudice their academic performance. 58,[64][65][66] Extremely low weight preterms most often have problems with mathematics (37% of children), followed by language difficulties in 24% and problems reading in 23%; and, in these same three areas, performance is even worse for children born below 750 g. 65 These cognitive deficiencies contribute to the high rates of repeated years at school (22-26%), requirements for special school (19-22%) or private tutoring (11-15%). 4 …”
Section: Prognosis At School Agementioning
confidence: 99%